Bobogyi a Burmese spiritual figure - Brac de La Perrière, Bénédicte; Munier-Gaillard, Cristophe; Stadtner, Donald Martin (River Books, 2019)
"Rich in Buddhist history and folklore, Bobogyi: A Burmese Spiritual Figure, is the first book dedicated to this Burmese nat, or guardian spirit, who features prominently in contemporary Burma (Myanmar). From an ethereal tree spirit to an established guardian at pagodas, the book examines the various trajectories of this ubiquitous figure. In the former capital of Yangon, bobogyi has been one of the main actors in the city's Buddhist landscape, beginning with the founding legend of the iconic Shwedagon Pagoda through his growing prominence since the 1990s following the city's recent urban expansion. With essays from two prominent scholars and a selection of detailed photographs that document the daily activities of worship and maintenance at bobogyi shrines, this charming book chronicles the history and modern-day relevance of bobogyi and also charts the ever-evolving nature of sacred narratives."